Pengaruh Corona Terhadap Freelance Designer di Surabaya - Florencia C. H.; Jesslyn J.; Tivany H.; Gilbert V. T.; Jeremy E. S. W.; Elbert W.; Joy C. F. N.; Christopher K. S. (Universitas Ciputra Surabaya, 2020)
This study aims to analyze the effect of corona on freelance designers in Surabaya. The effects caused by the coronavirus are many, including: panic buying, anxiety when traveling domestically and abroad, school schedules, lectures, and work becoming irregular and chaotic, some shops experiencing a decline in income, some workers being laid off, and of course this incident greatly affects businesses, including freelance designers. This study uses qualitative research methods, namely online interviews with several individuals who work as freelance designers. After doing research, it can be concluded that the COVID-19 pandemic does not have much effect on the sustainability of freelance designers. The results of these studies can be supported by existing research and theories. Keywords: corona, pandemic, freelancer designer, business.